Association of Borderline Personality Disorder and Antisocial Personality Disorders with Substance Use Disorder in a Teaching Hospital - Tariq, Tayyib; Ahmad Dogar, Imtiaz; Tariq, Muhammad Salman (Indus Journal of Bioscience Research, 2025)
Background: Substance use disorder is frequently associated with psychiatric comorbidity, particularly personality disorders, which can complicate treatment and worsen outcomes. Data on the prevalence and patterns of personality disorders among individuals with substance use disorder in Pakistan remain limited. Objective: To determine the frequency of Borderline Personality Disorder and Antisocial Personality Disorder and examine their association with sociodemographic factors among patients with substance use disorder. Methods: This cross-sectional study was conducted at a tertiary-care teaching hospital in Pakistan from 31 Dec 2024 to 31 May 2025. Male patients aged 18–60 years diagnosed with substance use disorder were recruited using consecutive sampling. Borderline Personality Disorder was assessed using the English version of the McLean Screening Instrument for Borderline Personality Disorder, while Antisocial Personality Disorder was diagnosed using the Urdu version of the Mini International Neuropsychiatric Interview (MINI 7.0.2). Sociodemographic and clinical data were collected using a structured proforma. Data were analyzed using descriptive statistics and chi-square tests. Results: A total of 88 participants were included. Borderline Personality Disorder was identified in 42.0% of participants, while Antisocial Personality Disorder was present in 58.0%. A significant comorbidity was observed between Borderline Personality Disorder and Antisocial Personality Disorder, with a higher proportion of individuals with Borderline Personality Disorder also meeting criteria for Antisocial Personality Disorder. Antisocial Personality Disorder was significantly more common among participants residing in rural areas, whereas no significant association was found between residence and Borderline Personality Disorder. Conclusion: Personality disorders, particularly Borderline Personality Disorder and Antisocial Personality Disorder, are highly prevalent among patients with substance use disorder, with substantial comorbidity between the two conditions. These findings highlight the importance of routine screening for personality disorders in substance use treatment settings and support the integration of comprehensive psychiatric assessment into addiction care.